Science Literacy Support for Improving Students Argumentation Skills - Irawan, Laura Alden Litha Miranda; Suyono, Suyono (Jurnal Pijar Mipa, 2024)
This study explores the impact of science literacy on improving students' argumentation skills at SMA Negeri 21 Surabaya during the 2023/2024 academic year, within the context of the "Merdeka Belajar" initiative and 21st-century competencies. This quantitative correlational research involved 60 students from classes XI-2 and XI-10, selected using purposive sampling techniques. Based on Toulmin's argument model and the PISA science literacy framework, data was collected through science literacy tests and argumentation skill assessments. Data analysis using Minitab 18 revealed a significant positive correlation between science literacy and argumentation skills, with p < 0.05 and correlation coefficients of 0.710 for class XI-2 and 0.926 for class XI-10. These findings support the hypothesis that enhancing science literacy can improve students' argumentation skills. This study highlights the importance of integrating argumentation skills into science education to enhance science literacy and recommends developing a curriculum that supports argumentation practices to improve students' critical thinking and problem-solving skills.